2017
DOI: 10.14198/jhse.2017.121.18
|View full text |Cite
|
Sign up to set email alerts
|

Self-assessment of physical fitness in adolescents

Abstract: Background: Physical fitness is an important indicator of the current and future health condition in adolescents. In comparison with institutional testing, self-assessment of physical fitness offers a number of benefits, including minimization or elimination of possible negative experience with inter-individual comparison in the context of motor diagnostics. The main objective of this paper is to determine the distribution normality of the resulting data and the intersexual differences in self-assessment of ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…However, the first article regarding fitness self-testing was published about 25 years ago (Knapik et al, 1992). Moving forward, research was nonexistent for 12 years (Corbin, 2004; Mikkelsson et al, 2005; Morgan et al, 2004), then, increased more recently (Graser et al, 2011; Huotari et al, 2009; Rubín et al, 2017). These studies concluded that: (a) HRF self-testing skills were important to students (Corbin, 2004) and could make students feel successful (Morgan et al, 2004); (b) students had positive perceptions of HRF testing, they understood the testing purpose of HRF testing, and made connections between the test results and their personal health (Graser et al, 2011); and (c) the sixth graders in Finland were able to accurately self-test their HRF (Huotari et al, 2009) while Rubín et al (2017) reported that 11–19 year old students in the Czech Republic could estimate their fitness well via self-testing.…”
Section: Self-testing Of Hrfmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the first article regarding fitness self-testing was published about 25 years ago (Knapik et al, 1992). Moving forward, research was nonexistent for 12 years (Corbin, 2004; Mikkelsson et al, 2005; Morgan et al, 2004), then, increased more recently (Graser et al, 2011; Huotari et al, 2009; Rubín et al, 2017). These studies concluded that: (a) HRF self-testing skills were important to students (Corbin, 2004) and could make students feel successful (Morgan et al, 2004); (b) students had positive perceptions of HRF testing, they understood the testing purpose of HRF testing, and made connections between the test results and their personal health (Graser et al, 2011); and (c) the sixth graders in Finland were able to accurately self-test their HRF (Huotari et al, 2009) while Rubín et al (2017) reported that 11–19 year old students in the Czech Republic could estimate their fitness well via self-testing.…”
Section: Self-testing Of Hrfmentioning
confidence: 99%
“…With the development of students’ self-testing skills, students may better understand HRF and this will likely have an effect on students’ negative attitudes toward fitness testing (Corbin, 2004; Graser et al, 2011; Rubín et al, 2017). Graser et al (2011) conducted a qualitative study using a written questionnaire, interviews, and field notes to examine fifth and sixth grade students’ perceptions of their experience participating in the Fitnessgram test organized in a self-testing format.…”
Section: Self-testing Of Hrfmentioning
confidence: 99%
See 3 more Smart Citations